The Effect of Using Pick List Evaluate Activate Supply End (Please) Strategy towards Students’ Ability in Writing Analytical Exposition Text at the Second Year of SMAN 1 Gunung Talang - Rani Belviati; Witri Oktavia (Journal of English Language Teaching, 2021)
The purpose of the research is to find out whether or not the PLEASE strategy is effective in the students’ ability in writing analytical exposition text at the second year of SMAN 1 Gunung Talang. This research uses a quantitative with quasi-experimental research with Pre-Test and Post-Test Control Group Design. The populations in this research were second year students’ of SMAN 1 Gunung Talang who were registered in the January-June period of the 2020/2021 school year. The research sample was 35 students of class XI IPA 1 as the experimental class and 35 students of class XI IPS 4 as the control class. The results of the analysis indicated that the mean of post-test score 85.37 was higher than the mean of pre-test score 67.23. Thus, in this research, the test scores were compared using of the t-test formula to determine the effectiveness of using PLEASE strategy ability in writing. Based on the data analysis and the results of the t-test, it was concluded that learning using PLEASE strategy was give the better effect to students ability in writing analytical exposition text at SMAN 1 Gunung Talang because tcount < ttable at a significant level of 0.05. So, it was concluded that the teaching of writing in the second year students of SMAN 1 Gunung Talang by using PLEASE strategy was better effect than without using PLEASE strategy. Keywords:PLEASE strategy, writing ability, analytical exposition